(untitled) - Mendelssohn, Kurt (New York, 1976)
This book introduce about the key to world domination, the conquest of the globe, divine beauty of simplicity, the turning-poit, power prodution, the crucial step, electromagnetism, the silent gaint, communication and computation, landfall in a new world, epilogue, select bibliography...
Keywords: Văn minh phương Tây,Civilization, Western; Lịch sử,History